Electronic Publishing: Emerging Trends - Bedi, D.S.; Vats, Geeta (DESIDOC Journal of Library & Information Technology, 2012)
Describes the electronic publishing concepts and their applications in scientific publishing. Highlights the electronic publishing technologies and the products that have given electronic publishing a prominent position in the marketplace. Consolidates the trends emerging in the field of Electronic publishing in the background of factors affecting both its promotion and inhibition.